Mitochondrial DNA copy number in autism spectrum disorder and attention deficit hyperactivity disorder: a systematic review and meta-analysis - Al-Kafaji, Ghada; Jahrami, Haitham Ali; Alwehaidah, Materah Salem; Alshammari, Yasmeen; Husni, Mariwan (Frontiers in Psychiatry, 2023)
Background Several reports suggest that altered mitochondrial DNA copy number (mtDNA-cn), a common biomarker for aberrant mitochondrial function, is implicated in autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD), but the results are still elusive. Methods A meta-analysis was performed to summarize the current indication and to provide a more precise assessment of the mtDNA-cn in ASD and ADHD. A search in the MEDLINE-PubMed, Scopus, and EMBASE databases was done to identify related studies up to the end of February 2023. The meta-analysis was conducted according to recommendations of the Cochrane Handbook of Systematic Reviews. Results Fourteen studies involving 666 cases with ASD and ADHD and 585 controls were collected and judged relevant for the systematic review and meta-analysis. The pooled results by a random effects meta-analysis was reported as a geometric mean of the estimated average response ratio and 95% confidence interval. Overall analysis of studies reported differences in mtDNA-cn in blood samples (k = 10) and non-blood samples (brain tissues and oral samples; k = 4) suggested significantly higher mtDNA-cn in patients compared to controls (p = 0.0275). Sub-analysis by stratifying studies based on tissue type, showed no significant increase in mtDNA-cn in blood samples among patients and controls (p = 0.284). Conversely, higher mtDNA-cn was observed in non-blood samples in patients than in controls (p = 0.0122). Further stratified analysis based on blood-cell compositions as potential confounds showed no significant difference in mtDNA-cn in peripheral blood samples of patients comparted to controls (p = 0.074). In addition, stratified analysis of aged-matched ASD and ADHD patients and controls revealed no significant difference in mtDNA-cn in blood samples between patients and controls (p = 0.214), whereas a significant increase in mtDNA-cn was observed in non-blood samples between patients and controls (p < 0.001). Finally, when the mtDNA-cn was analyzed in blood samples of aged-matched patients with ASD (peripheral blood, leukocytes, and PBMCs) or ADHD (peripheral blood), no significant difference in mtDNA-cn was observed between ASD patients and controls (p = 0.385), while a significant increase in mtDNA-cn was found between ADHD patients and controls (p = 0.033). Conclusion In this first meta-analysis of the evaluation of mtDNA-cn in ASD/ADHD, our results show elevated mtDNA-cn in ASD and ADHD, further emphasizing the implication of mitochondrial dysfunction in neurodevelopmental disorders. However, our results indicate that the mtDNA-cn in blood is not reflected in other tissues in ASD/ADHD, and the true relationship between blood-derived mtDNA-cn and ASD/ADHD remains to be defined in future studies. The importance of blood-cell compositions as confounders of blood-based mtDNA-cn measurement and the advantages of salivary mtDNA-cn should be considered in future studies. Moreover, the potential of mtDNA-cn as a biomarker for mitochondrial malfunction in neurodevelopmental disorders deserves further investigations.